The role of social media in promoting the activities of the personal trainer - Domański, Jarosław; Stefaniak, Tadeusz; Wesołowski, Daniel; Mauer-Różańska, Renata; Mardausz, Anna (Journal of Education, Health and Sport, 2022)
Work in which the focus was on precisely identifying specific social media aimed at promoting personal trainers. Two of the largest social media, which bring together communities with similar interests and needs, are listed. What marketing tools should be used to precisely define the "target" of the personal trainer. The processes of planning and implementing sales ideas. Identifying the characteristics of social-media. Assessment of the usefulness of social media in the promotion of personal trainers. Conclusions Based on the research, the following conclusions could be drawn. 1. Social media is a powerful marketing tool nowadays and should be an integral part of the trainers’ marketing strategy. 2. Women use social media more often and are more willing to participate in research and discussions on a healthy lifestyle, they are more open than men. There are more of them in fitness groups, so when planning their activities on the Internet, trainers should take into account women’s preferences and try to run their fun pages in such a way that they are interesting for them. 3. The younger generation is better acquainted with social media and uses it more willingly. People over 30 years of age, that is generations X and Y, were brought up in a time when access to the Internet and social media was impossible or severely limited, therefore it is not a standard for them and they do not use them on a daily basis. [Fries, Kimberly 2017, 5 Reasons Why Millennial Leaders Need Performance Feedback, Forbes] 4. The vast majority of respondents (98%) admitted that they use social media. This shows the universality of this method of interpersonal communication. 5. The most used social media are Instagram and Facebook. There are certain trends on the Internet, and Internet users communicate with each other and set up accounts on portals that are currently popular among other users. 6. More than half of the respondents admitted that they use the help of personal trainers. This shows how much personal trainers have a huge impact on physically active people. 7. Social media is an effective means of gaining popularity, so personal trainers should use them for that purpose. Nowadays, almost everyone uses the Internet and communicates via various social media, so keeping profiles on them is a very good way to reach a large number of users. 8. Particularly desired by people interested in the subject of fitness and following the actions of their chosen personal trainers are the effects of work with the mentees, which the trainers publish on their profiles. Their physical characteristics are almost as important. 9. A large part of personal trainers use social media for marketing purposes. 10. The most frequently chosen portal by personal trainers is Instagram, its use is extremely simple, and the greatest emphasis is placed on publishing photos, which allows sharing various values ​​in a quick and easy way. Facebook, which has been one of the main networking platforms among Internet users for years, came in second. 11. The main feature of social media that coaches pay the most attention to when planning their marketing strategy is popularity. They gather the largest number of users at any given time, which may translate into gaining more new recipients. Simplicity and functionality also turned out to be important. 12. Most of the trainers say that they think social media is very useful for image building and facilitates the customer acquisition process. 13. Contact between people and enabling them to freely discuss on the Internet is one of the functions that personal trainers consider the most important in social media. 14. For the optimal use of the power of social media, more than one distribution channel should be used simultaneously. 15.80% of trainers follow other trainers on social media. 16. Few of the coaches copy the content of their colleagues, slightly more than 7% of the coaches admitted it. However, these data may be biased, despite the fact that the survey was conducted anonymously. Many people do not want to admit even to themselves that they have acted unethically.